The chemokine receptor CXCR6 contributes to recruitment of bone marrow-derived fibroblast precursors in renal fibrosis - Xia, Yunfeng (2014)
Bone marrow-derived fibroblasts in circulation are of hematopoietic origin, proliferate, differentiate into myofibroblasts, and express the chemokine receptor CXCR6. Since chemokines mediate the trafficking of circulating cells to sites of injury, we studied the role of CXCR6 in mouse models of renal injury. Significantly fewer bone marrow-derived fibroblasts accumulated in the kidney of CXCR6 knockout mice in response to injury, expressed less profibrotic chemokines and cytokines, displayed fewer myofibroblasts, and expressed less α-smooth muscle actin in the obstructed kidneys compared with wild-type mice. CXCR6 deficiency inhibited total collagen deposition and suppressed expression of collagen I and fibronectin in the obstructed kidneys. Furthermore, wild type mice engrafted with CXCR6(−/−) bone marrow cells displayed fewer bone marrow-derived fibroblasts in the kidneys with obstructive injury and showed less severe renal fibrosis compared with wild-type mice engrafted with CXCR6(+/+) bone marrow cells. Transplant of wild type bone marrow into CXCR6(−/−) recipients restored recruitment of myeloid fibroblasts and susceptibility to fibrosis. Hematopoietic fibroblasts migrate into injured kidney and proliferate and differentiate into myofibroblasts. Thus, CXCR6, together with other chemokines and their receptors, may play important roles in the recruitment of bone marrow-derived fibroblast precursors into the kidney and contribute to the pathogenesis of renal fibrosis.